Role of metallic packing and kinetic promoter in designing a hydrate-based gas separation process - Kumar, Asheesh; Kumar, Rajnish (Energy & Fuels, 2015)
In the present work, kinetics of the hydrate-based gas separation (HBGS) process has been studied employing an unstirred reactor configuration. Gas uptake measurements were carried out for studying hydrate formation kinetics and final water to hydrate conversion using fuel gas mixtures (mixture 1, 40.4% CO2 + 59.6% H-2; mixture 2, 40.9% CO2 + 58.05% H-2 + 1.05% H2S). Silica sand and stainless-steel-structured packing (SSP) were used as contact media in the presence of an anionic surfactant sodium dodecyl sulfate (SDS) as a kinetic promoter. Experiments were conducted with three different concentrations of SDS in water to enhance hydrate formation kinetics. On the basis of induction time and rate of hydrate growth, 1 wt % SDS was determined to be the best concentration for carbon dioxide capture at 7.0 MPa and 273.65 K from the CO2 + H-2 gas mixture. In comparison to silica sand packing, use of SSP was found to improve the final water to hydrate conversion (71.0 +/- 4.1%). The addition of H2S impurity in the fuel gas mixture was also found to enhance the rate of hydrate formation in the presence of SDS at 7.8 MPa and 274.5 K. On the basis of the experimental results and our previous studies on separation efficiency, a continuous HBGS process is proposed to separate CO2 and produce CO2- and H2S-free H-2 stream from a fuel gas mixture.

Role of surfactants in promoting gas hydrate formation - Kumar, Asheesh; Bhattacharjee, Gaurav; Kulkarni, B. D.; Kumar, Rajnish (Industrial & Engineering Chemistry Research, 2015)
Gas hydrates have been proposed as a potential technology for a number of applications, such as separation of gas mixtures, CO2 capture, transportation, and sequestration, methane storage and transport, and seawater desalination. Most of these applications will benefit from reduced induction time of hydrate nucleation, enhanced hydrate growth rate, and maximum water-to-hydrate conversion. The addition of surfactants to the gas-water system serves this purpose in a very effective manner. This review focuses on different surfactants that were utilized for gas hydrate formation studies; insights have been provided on the possible mechanisms of action through which these surfactants affect hydrate formation kinetics. A thorough analysis of the existing literature on surfactants suggests that enhanced rate of hydrate nucleation and growth kinetics may not be directly linked to micelle formation. Conversely, reduced surface tension in the presence of surfactants not only enhances the mass transfer but also changes the morphology of hydrate formation, which in turn enhances gas-water interactions for faster hydrate growth rate.